Did tsunamis lead to changes in ocean properties? a revisit - Bunson, Samuel; Hu, Chuanmin (Frontiers in Marine Science, 2023)
Natural disasters such as earthquakes and/or tsunamis may cause disturbance to the ocean, which can possibly lead to changes in the ocean properties. Here, we review the literature for the reported pre- or post-event changes of such properties, which include chlorophyll-a concentration, temperature, and turbidity in the surface ocean. Most of the reported changes were based on remotely sensed ocean properties, and such changes were attributed to the ocean’s response to the events. Here, by using the same remote sensing data collected in non-event years as the ‘control’ experiments or by analyzing the same remote sensing data at different spatial scales, however, it is found that similar changes also occurred in non-event years or could not be observed at different spatial scales. Therefore, the before-after changes detected in remote sensing imagery do not appear to be sufficient to infer causality but are more likely a result of natural variability.